The importance of internal and external features in recognizing faces that vary in familiarity and race. (November 2022) - Latif, Menahal; Moulson, Margaret C.
Familiar and unfamiliar faces are recognized in fundamentally different ways. One way in which recognition differs is in terms of the features that facilitate recognition: previous studies have shown that familiar face recognition depends more on internal facial features (i.e., eyes, nose and mouth), whereas unfamiliar face recognition depends more on external facial features (i.e., hair, ears and contour). However, very few studies have examined the recognition of faces that vary in both familiarity and race, and the reliance on different facial features, whilst also using faces that incorporate natural within-person variability. In the current study, we used an online version of the card sorting task to assess adults' ( n = 258) recognition of faces that varied in familiarity and race when presented with either the whole face, internal features only, or external features only. Adults better recognized familiar faces than unfamiliar faces in both the whole face and the internal features only conditions, but not in the external features only condition. Reasons why adults did not show an own-race advantage in recognition are discussed.